Osteogenic index of step exercise depending on choreographic movements, session duration, and stepping rate - Santos-Rocha, R. A.; Oliviera, C. S.; Veloso, A. P. (British Journal of Sports Medicine, 2006)
Background: Step exercise has been promoted as a low impact physical activity recommended for the improvement of cardiorespiratory and muscular fitness. This recreational activity might also be recommended to improve bone health since mechanical load plays an important role in the normal development of the skeleton.